ANALISIS KETERLAMBATAN PEMBANGUNAN TOL DENGAN METODE STOKASTIK DAN MITIGASI RISIKO - Muhammad Iqbal (LPPM Universitas Abdurrab, 2020)
Based on information accuired from contractor and project owner, this Toll Road Contruction has experienced significant delay in its completion. The purpose of this case strudy is to identified, asses simulate and reduce delay risk in Toll Road Contruction using stochastic method and mitigation risk. In fact, there are some article about delay analysis related to toll road contruction, but in this case study with combining 2 analysis method it is expected to provide more input for researchers. The results of mitigation in this project duration delay are relatively maximum and in accordance with the research objectives. From risk identification, there are 9 risk that affect the performance of time. Some of the highest risk that have biggest impact on performance of time such as land accuisition, inadequate investigation work before design and inacurrate survey during pre – design. Risk analysis based on stochastic analysis found that with 90% of confidence level, the possibility of this project can be completed in 782-821 days, in its realization this Toll Road Contruction faced delay up to 1112 day (probabability of occurrence was above 95%).